Green compound scale inhibitor for geothermal fluid and preparation method thereof

By using modified polyaspartic acid, highly hydrolyzed polymaleic anhydride, polyepoxysuccinic acid and polyacrylic acid in geothermal fluids, the problem of poor effect of existing scale inhibitors in high alkalinity or high mineralization geothermal fluids is solved, and better scale inhibition performance and biodegradability are achieved.

CN119735313AActive Publication Date: 2025-04-01TIANJIN GEOTHERMAL EXPLORATION & DEV DESIGNING INST +2

Patent Information

Application Number
CN202411756659.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-01
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The scale inhibitors used in existing geothermal waters have problems such as environmental pollution and poor scale inhibition in high alkalinity or high mineralization geothermal fluids.

Method used

Complex scale inhibitors including modified polyaspartic acid, highly hydrolyzed polymaleic anhydride, polyepoxysuccinic acid and polyacrylic acid are used to achieve scale inhibition effects through chelation solubilization and lattice distortion mechanisms.

Benefits of technology

It significantly improves the biodegradability and scale resistance of scale inhibitors, and is suitable for geothermal fluids with high alkalinity and high mineralization, reducing pollution to the ecological environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735313A_ABST
    Figure CN119735313A_ABST
Patent Text Reader

Abstract

The invention provides a green compound scale inhibitor for geothermal fluid. The compound scale inhibitor comprises modified polyaspartic acid, high-hydrolysis polymaleic anhydride, polyepoxysuccinic acid and polyacrylic acid. According to the environment-friendly compound scale inhibitor for the geothermal fluid, the modified polyaspartic acid, the high-hydrolysis polymaleic anhydride, the polyepoxysuccinic acid and the polyacrylic acid are compounded, a good synergistic effect is achieved, scale inhibition is achieved through chelation solubilization and lattice distortion, the scale inhibition advantage in actual geothermal water is obvious, and the environment-friendly compound scale inhibitor has a good actual popularization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the geothermal field, and in particular relates to a green compound antiscalant for geothermal fluid and a preparation method thereof. Background Art

[0002] As a non-carbon-based, clean energy, geothermal energy has the advantage of stable and continuous output, and is of great value in achieving the development goals of "carbon peak" and "carbon neutrality". In the process of formation, geothermal water dissolves rich minerals. Highly mineralized geothermal water will cause scaling to geothermal well pipes, well pumps, transmission pipelines, heat exchange, heat-using equipment, etc., affecting geothermal utilization.

[0003] The method of adding chemical agents to geothermal water to prevent the formation of geothermal water scale has a long history. Adding scale inhibitors is generally considered to be the most direct and effective method to prevent scaling. Scale inhibitors can be divided into natural polymer scale inhibitors and synthetic polymer scale inhibitors according to their ingredients. Synthetic polymer scale inhibitors can be further divided into phosphorus-containing polymer scale inhibitors, carboxylic acid polymer scale inhibitors, sulfonic acid polymer scale inhibitors and environmentally friendly scale inhibitors. In the past few decades, phosphorus-containing scale inhibitors have been the most widely used. However, this type of scale inhibitor will cause secondary pollution to the environment, and the agent needs to be recovered and treated immediately, especially during the geothermal water recharge process, which will pollute groundwater and soil and cause harm to the ecological environment.

[0004] At the same time, a single type of scale inhibitor is difficult to have a good comprehensive scale inhibition and dispersion effect in a complex geothermal fluid system composed of multiple ions during actual application. At present, the research on environmentally friendly compound scale inhibitors is mainly focused on the scale inhibition of power plant circulating cooling water, boiler water, etc., while there are few studies on green scale inhibitors for geothermal water. Summary of the invention

[0005] In view of this, the present invention aims to overcome the defects in the prior art and proposes a green compound antiscalant for geothermal fluid and a preparation method thereof.

[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A green compound antiscalant for geothermal fluid, characterized in that the compound antiscalant comprises the following raw materials in parts by weight:

[0008]

[0009] Preferably, the compound antiscalant comprises the following raw materials in parts by weight:

[0010]

[0011] More preferably, the compound antiscalant comprises the following raw materials in parts by weight:

[0012]

[0013] Furthermore, the preparation method of the modified polyaspartic acid comprises the following steps: mixing dextran, polysuccinimide and a catalyst, reacting under heating conditions, and washing, filtering and drying the reaction product after the reaction is completed to obtain the modified polyaspartic acid.

[0014] Furthermore, the catalyst is prepared by mixing p-toluenesulfonic acid and dimethyl sulfoxide; the solid-liquid ratio of p-toluenesulfonic acid to dimethyl sulfoxide is 0.1-0.12 g: 100-120 mL.

[0015] Furthermore, the mass ratio of the dextran, polysuccinimide and catalyst is 1-1.2 g: 2-2.5 g: 100-120 mL.

[0016] Furthermore, the temperature of the heating step is 120-125° C., the reaction time is 20-24 hours, and the molecular weight of the dextran is 1000.

[0017] Furthermore, the preparation method of the highly hydrolyzed polymaleic anhydride comprises the following steps: adding maleic anhydride, sodium hydroxide and ammonium ferric sulfate into deionized water, stirring until completely dissolved, adding hydrogen peroxide dropwise thereto under heating conditions, and cooling to room temperature after the reaction is completed to obtain the highly hydrolyzed polymaleic anhydride.

[0018] The molecular weight of the hydrolyzed polymaleic anhydride is 1500-2000.

[0019] Furthermore, the solid-liquid ratio of maleic anhydride, sodium hydroxide, ammonium ferric sulfate, hydrogen peroxide and deionized water is 400-500g: 100-105g: 0.04-0.06g: 400-500mL: 450-500mL; the mass concentration of the hydrogen peroxide is 30%.

[0020] Furthermore, the temperature of the heating step is 95-100° C.; the time of the reaction step is 3-4 hours; and the speed of the dropping step is 50-60 drops / min.

[0021] Hydrolyzed polymaleic anhydride and polyacrylic acid are both highly efficient, phosphorus-free green scale inhibitors, and both belong to carboxylic acid polymers. The carboxylic acid functional groups in the polymer can form soluble chelates with calcium ions, thereby inhibiting the formation of calcium carbonate nuclei. Hydrolyzed polymaleic anhydride and polyacrylic acid have a synergistic effect, and the scale inhibition effect of the copolymer of the two is significantly better than that of a single scale inhibitor. However, the compound scale inhibitor of hydrolyzed polymaleic anhydride and polyacrylic acid has the following disadvantages: 1. Both hydrolyzed polymaleic anhydride and polyacrylic acid are bio-refractory organic matter, and will still cause certain pollution to the ecological environment during the utilization and reinjection of geothermal water; 2. The commercially available hydrolyzed polymaleic anhydride is the product of partial hydrolysis of polymaleic anhydride, and about 60-70% of the anhydride structure is hydrolyzed into carboxylic acid, which is not completely hydrolyzed, has a low molecular weight, and has the problem of large dosage; 3. The compound scale inhibitor of hydrolyzed polymaleic anhydride and polyacrylic acid has a general scale inhibition effect in high-alkalinity geothermal fluids; 4. In geothermal fluids with high mineralization, there are a large number of scale-forming ions and ions that interfere with scale inhibition, and the compound scale inhibitor of hydrolyzed polymaleic anhydride and polyacrylic acid has a general scale inhibition effect.

[0022] Therefore, the present invention adds biodegradable polyepoxysuccinic acid and modified polyaspartic acid suitable for high alkalinity water systems on the basis of the compound of hydrolyzed polymaleic anhydride and polyacrylic acid. On the one hand, the amount of hydrolyzed polymaleic anhydride and polyacrylic acid can be reduced, the biodegradability of the compound scale inhibitor can be improved, and the pollution to the ecological environment caused by the compound scale inhibitor during the utilization and reinjection of geothermal water can be further reduced. On the other hand, the four scale inhibitors work synergistically, and the scale inhibition performance of the compound scale inhibitor is significantly increased. The number of active growth points for calcium carbonate scaling is limited. When the scale inhibitor molecules cover a certain active growth point, the activity of the point will be inhibited. Polyacrylic acid contains a large number of carboxyl groups, hydrolyzed polymaleic anhydride contains a large number of carboxyl groups and hydroxyl groups, modified polyaspartic acid contains a large number of carboxyl groups, amino groups, hydroxyl groups and glycosidic bonds, and polyepoxysuccinic acid contains a large number of carboxyl groups, hydroxyl groups and ether bonds. The compound scale inhibitor covers the calcium ions of calcium carbonate scale through the unpaired electrons of N and O atoms in these groups, and covers the calcium carbonate ions of calcium carbonate scale through hydrogen bonding. The combination of these two strong non-bonding interactions will cause the scale inhibitor molecules to be closely attracted to the active sites on the surface of calcium carbonate, so that the four scale inhibitors can play a good synergistic scale inhibition effect. In addition, these groups are embedded or adsorbed on the surface of calcium carbonate crystal nuclei, which increases the negative charge density on the surface of the crystal nuclei, increases the potential of the crystal nuclei, and increases the Coulomb repulsion between the crystal nuclei, thereby significantly hindering the formation and growth of calcium carbonate crystal nuclei. Moreover, the spatial structures of the four polymers are different. They are embedded or adsorbed on the surface of calcium carbonate crystal nuclei to form a complex network structure, which plays a role of steric hindrance, resulting in obvious distortion of the calcium carbonate lattice, further hindering the growth of calcium carbonate crystal nuclei.

[0023] At the same time, the embedding or adsorption of hydrolyzed polymaleic anhydride on calcium carbonate crystals mainly relies on the double bond O atoms in maleic acid or the -OH groups in maleic acid, so the degree of approach of polymers with different degrees of hydrolysis to calcium carbonate crystals is different, and the change of energy is also different. Studies have shown that as the degree of hydrolysis increases, polymer molecules are closer to calcium carbonate crystals, the change of active group bond distance is more obvious, and the energy decrease is also greater, that is, the scale inhibition effect is more obvious. Therefore, the present invention improves the hydrolysis degree of polymaleic anhydride by first neutralizing maleic anhydride during the synthesis process of hydrolyzed polymaleic anhydride, thereby improving the scale inhibition effect of hydrolyzed polymaleic anhydride.

[0024] Moreover, polyaspartic acid is not resistant to high temperatures and is not suitable for high-temperature geothermal fluids, so it needs to be modified. Considering that polysaccharide compounds have strong affinity and good water solubility, and contain a large number of hydroxyl groups in the molecular structure, the esterification reaction of hydroxyl and carboxyl groups to form esters is one of the most common reactions in organic synthesis. Therefore, the present invention obtains polyaspartic acid monomers of α and β configurations through the nucleophilic attack of the CN bond of polysuccinimide by the nucleophilic reagent dimethyl sulfoxide, and uses the hydroxyl groups in the polyaspartic acid molecules to modify the carboxyl groups in the polyaspartic acid molecules, thereby realizing the green modification of polyaspartic acid by polysaccharide. Due to the large number of hydroxyl groups and hydrophobic carbon rings on the sugar chain, dextran exhibits a highly ordered spiral structure in aqueous solution; after being modified with dextran, hydroxyl groups and spiral structures are introduced into polyaspartic acid, and the unpaired electrons of the O atoms in the hydroxyl groups are embedded or adsorbed on the surface of the calcium carbonate nucleus in a physical and chemical way, increasing the negative charge density on the surface of the nucleus, increasing the potential of the nucleus, and increasing the Coulomb repulsion between the nuclei, effectively hindering the formation of calcium carbonate nuclei; coupled with the spiral structure of the modified polyaspartic acid, the calcium carbonate lattice distortion is further aggravated, thereby significantly hindering the growth of the calcium carbonate nucleus, therefore, the scale inhibition effect of polyaspartic acid modified with dextran is significantly improved. In addition, dextran has good water solubility and biodegradability. The use of dextran to modify polyaspartic acid can improve the effect of the compound scale inhibitor while ensuring the biodegradability of the modified polyaspartic acid.

[0025] The compound antiscalant of the present invention also exhibits good antiscaling effect in high alkalinity geothermal water. 3 - The ionization equilibrium of CO shifts to the right. 3 2-As the content increases, calcium carbonate precipitation is easily formed, and calcium hydroxide precipitation is also generated, which leads to a decrease in the scale inhibition effect of the scale inhibitor. However, with the increase of pH, the dissociation of polyepoxysuccinic acid is enhanced, the charge density on the molecular chain increases, and the ductility of the molecular chain increases, which can be expanded from a curled structure to an extended structure. The negatively charged groups are fully exposed to the outside, which is conducive to adsorption on the microcrystals of calcium carbonate scale bound by ion bonds, thereby inhibiting the further growth of calcium carbonate scale crystals. After being modified with dextran, polyaspartic acid has a helical structure. In high-alkalinity geothermal water, it can unwind to form an irregular curled state, exposing more negatively charged groups to the outside, better adsorbing on the microcrystals of calcium carbonate scale bound by ion bonds, and exerting a good scale inhibition effect.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] The green compound scale inhibitor for geothermal fluid described in the present invention is a compound of modified polyaspartic acid, highly hydrolyzed polymaleic anhydride, polyepoxysuccinic acid and polyacrylic acid, which has good synergistic effect, wide temperature adaptability and acid and alkali resistance, and achieves scale inhibition through chelating solubilization and lattice distortion. It has obvious scale inhibition advantages in actual geothermal water and has good practical promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The SEM images before and after the use of the compound antiscalant described in Example 1 of the present invention are as follows: A is before adding the antiscalant, and B is after adding the antiscalant;

[0029] Figure 2 The XRD diagrams before and after the use of the compound antiscalant according to the embodiment of the present invention are shown in Figure 1. A is before adding the antiscalant, and B is after adding the antiscalant.

[0030] Figure 3 It is a bar graph of the scale inhibition rate of the compound scale inhibitor described in Examples 1-2 of the present invention and Comparative Examples 1-4;

[0031] Figure 4 It is a bar graph of the scale inhibition rate of the compound scale inhibitor described in Example 1 of the present invention and Comparative Example 1 at different temperatures;

[0032] Figure 5 This is a bar graph of the scale inhibition rate of the composite scale inhibitor described in Example 1 of the present invention at different pH values. DETAILED DESCRIPTION

[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0034] The present invention will be described in detail below with reference to the embodiments.

[0035] Example 1

[0036] A green compound antiscalant for geothermal fluid comprises the following raw materials in parts by weight: 4 parts of modified polyaspartic acid, 12 parts of highly hydrolyzed polymaleic anhydride, 4 parts of polyepoxysuccinic acid, and 4 parts of polyacrylic acid.

[0037] The preparation method of the modified polyaspartic acid comprises the following steps: mixing 1.0 g of dextran (molecular weight 1000), 2.0 g of polysuccinimide and a catalyst (the catalyst is a mixture of 0.1 g of p-toluenesulfonic acid and 100 mL of dimethyl sulfoxide), turning on a stirrer, heating to 120° C., reacting for 24 hours, and after the reaction is completed, washing the reaction product with anhydrous ethanol, filtering, and drying to obtain the modified polyaspartic acid.

[0038] The preparation method of the highly hydrolyzed polymaleic anhydride comprises the following steps: adding 500g of maleic anhydride, 102g of sodium hydroxide and 0.04g of ammonium ferric sulfate into 450mL of deionized water, turning on a stirrer, heating the water to 40-50°C, stirring the water until the water is completely dissolved, and then heating the water to 95-100°C, dripping 400mL of hydrogen peroxide (mass concentration 30%) into the water at a dripping speed of 50-60 drops / min, starting the timing after the hydrogen peroxide is completely titrated, reacting for 3-4 hours, and cooling the water to room temperature after the reaction is completed to obtain the highly hydrolyzed polymaleic anhydride having a molecular weight of 1500-2000.

[0039] A method for preparing a green composite scale inhibitor for geothermal fluid comprises the following steps: weighing 0.5g of highly hydrolyzed polymaleic anhydride, dissolving it in 100ml of deionized water, to obtain solution A; weighing 0.5g of modified polyaspartic acid, dissolving it in 100ml of deionized water, to obtain solution B; weighing 0.55g of polyepoxysuccinic acid (90%), dissolving it in 100ml of deionized water, to obtain solution C; weighing 0.5g of polyacrylic acid (molecular weight 5000), dissolving it in 100ml of deionized water, to obtain solution D; at room temperature, taking 1.2ml of solution A, 0.4ml of solution B, 0.4ml of solution C and 0.4ml of solution D to mix to obtain a composite scale inhibitor, which can be used to effectively inhibit scale in 500-1000ml of geothermal water.

[0040] The morphological evolution of calcium carbonate scale after adding the compound scale inhibitor described in Example 1 and without adding the scale inhibitor is as follows: Figure 1 As shown. Figure 1As shown in Figure A, when no compound scale inhibitor is added, the crystals are regular cubes with tight and orderly arrangement, which is the typical appearance of calcite. The compound scale inhibitor contains a large number of N, O atoms and hydrogen bonds with unpaired electrons. The scale inhibitor molecules cover the calcium ions of calcium carbonate scale through these N and O atoms, and cover the calcium carbonate ions of calcium carbonate scale through hydrogen bonds. The combination of these two strong non-bonding interactions will cause the scale inhibitor molecules to be tightly attracted to the active sites on the surface of calcium carbonate, allowing the four scale inhibitors to exert a good synergistic scale inhibition effect. In addition, these groups are embedded in or adsorbed on the surface of the calcium carbonate nucleus, which increases the negative charge density on the surface of the nucleus, increases the potential of the nucleus, and increases the Coulomb repulsion between the nuclei, thereby significantly hindering the formation and growth of the calcium carbonate nucleus. Moreover, the spatial structures of the four polymers are different. They are embedded in or adsorbed on the surface of the calcium carbonate nucleus to form a complex network structure, which plays a role of steric hindrance, resulting in obvious distortion of the calcium carbonate lattice, further hindering the growth of the calcium carbonate nucleus. Figure 1 As shown in Figure B, after adding the compound scale inhibitor, defects appeared on the edge of the crystal, the growth pattern gradually became irregular, broken or loose, with different shapes and small size, indicating that the composite scale inhibitor affected the nucleation and growth process of the calcium carbonate crystal. This may be because the composite scale inhibitor is embedded or adsorbed on the surface of the calcium carbonate crystal, making it unable to grow in a normal way, resulting in its structure being relatively loose, small, with different appearances and easy to break.

[0041] XRD was used to analyze the crystal structure of calcium carbonate formed without and with antiscalant. The results are as follows: Figure 2 As shown. When no scale inhibitor is added, the calcium carbonate crystals produced after 10 hours of constant temperature have characteristic peaks of calcite at diffraction angles of 2θ at 23.02°, 29.47°, 31.42°, 35.97°, 39.40°, etc., indicating that the crystal form of calcium carbonate is basically the most stable calcite. After adding the scale inhibitor and keeping the temperature constant for 10 hours, the intensity of the characteristic absorption peak of calcite is significantly reduced, and the characteristic peaks of metastable vaterite and aragonite appear at 2θ at 26.21°, 27.21°, 32.74° and 45.85°, and the crystal form is calcite, vaterite and aragonite structure. Since the characteristic absorption peak of calcite is significantly reduced, it can be inferred that after the addition of the scale inhibitor, the calcium carbonate crystals are transformed from stable calcite to unstable vaterite and aragonite, indicating that the addition of the scale inhibitor causes the lattice of calcium carbonate to be distorted.

[0042] In addition, the static scale inhibition experiment found that the calcium carbonate crystals at the bottom of the flask without scale inhibitors were dense white precipitates that were not easy to wash off, while the calcium carbonate precipitates at the bottom of the beaker with scale inhibitors were soft and flocculent and could be washed off with a little shaking. Combining the static scale inhibition experiment, the electron microscope scanning photos of the scale samples and the relevant theories of scale inhibition mechanism, it was analyzed that the scale inhibition mechanism is mainly achieved through the two effects of chelation solubilization and lattice distortion.

[0043] Example 2

[0044] The only difference from Example 1 is that the following raw materials are included in parts by weight: 4 parts of modified polyaspartic acid, 10 parts of highly hydrolyzed polymaleic anhydride, 4 parts of polyepoxysuccinic acid, and 5 parts of polyacrylic acid.

[0045] Comparative Example 1

[0046] The only difference from Example 1 is that the modified polyaspartic acid is replaced by conventional commercially available polyaspartic acid.

[0047] Comparative Example 2

[0048] The only difference from Example 1 is that the highly hydrolyzed polymaleic anhydride is replaced by conventional commercially available hydrolyzed polymaleic anhydride.

[0049] Comparative Example 3

[0050] The only difference from Example 1 is that the modified polyaspartic acid is replaced by conventional commercially available polyaspartic acid, and the highly hydrolyzed polymaleic anhydride is replaced by conventional commercially available hydrolyzed polymaleic anhydride.

[0051] Comparative Example 4

[0052] The only difference from Example 1 is that the added amount of modified polyaspartic acid is 7 parts, the added amount of highly hydrolyzed polymaleic anhydride is 7 parts, the added amount of polyepoxysuccinic acid is 7 parts, and the added amount of polyacrylic acid is 7 parts.

[0053] The scale inhibitors obtained in Examples 1-2 and Comparative Examples 1-4 were subjected to the following experiments:

[0054] 1. Determine the scale inhibition rate of the compound scale inhibitor with reference to the national standard "Determination of scale inhibition performance of water treatment agents: calcium carbonate precipitation method" (GB / T 16632-2019). Take the geothermal fluid taken from a geothermal well in Tianjin as the background water body. Table 1 shows the main chemical components and contents of the geothermal fluid. Add 240 mg / L CaCl 2 (Ca 2+ ), 732mg / L NaHCO 3 The scale inhibition rates of the scale inhibitors of the embodiments and comparative examples are as follows: Figure 3 As shown, the reaction temperature is 80°C and the reaction time is 10h.

[0055] Table 1 Contents of main chemical components of geothermal fluid from a geothermal well in Tianjin

[0056] Analyze Project Concentration (mg / L) Analyze Project Concentration (mg / L) Analyze Project Concentration (mg / L) <![CDATA[Na + ]]> 228 <![CDATA[SO 4 2- ]]> 163 Total Alkalinity 263 K+ 56.6 <![CDATA[HCO 3 - ]]> 317 Total hardness 89.1 <![CDATA[Ca 2+ ]]> 25.3 <![CDATA[CO 3 2- ]]> 1.8 Mineralization 1020 <![CDATA[Mg 2+ ]]> 6.37 Cl 137 solid matter 861.5 <![CDATA[Fe 2+ ]]> 0.24 <![CDATA[NO 3 - ]]> 0.27 <![CDATA[SiO 2 ]]> 85.6 <![CDATA[Free CO 2 > 0 <![CDATA[P0 4 3- ]]> 0.02 pH 8.33 F 7.77

[0057] like Figure 3As shown, the scale inhibition rate of the compound scale inhibitor prepared in Example 1 is significantly higher than the scale inhibition rate of the compound scale inhibitor prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 3, indicating that the modified polyaspartic acid and highly hydrolyzed polymaleic anhydride significantly improve the scale inhibition effect of the compound scale inhibitor. The scale inhibition rate of the compound scale inhibitor prepared in Example 1 and Example 2 is significantly higher than the scale inhibition rate of the compound scale inhibitor prepared in Comparative Example 4, indicating that optimizing the dosage and ratio of the four scale inhibitors can significantly improve the scale inhibition effect of the compound scale inhibitor.

[0058] 2. The scale inhibition rate of the compound scale inhibitor was determined according to the national standard "Determination of scale inhibition performance of water treatment agents: calcium carbonate precipitation method" (GB / T 16632-2019). The geothermal fluid taken from a geothermal well in Tianjin was used as the background water body. The main chemical components and contents of the geothermal fluid are shown in Table 1. 240 mg / L CaCl was added to the geothermal water. 2 (Ca 2+ Calculated), 732mg / LNaHCO 3 The scale inhibitors of Example 1 and Comparative Example 1, other reaction conditions remain unchanged, and the reaction temperatures are 40°C, 60°C, 80°C, 100°C, and 120°C. Figure 4 shown.

[0059] Depend on Figure 4 It can be seen that within the range of 40-120°C, the scale inhibition rate of the compound scale inhibitor prepared in Example 1 is above 90%, which shows that the compound scale inhibitor has a wide temperature application range. At temperatures of 80°C, 100°C and 120°C, the scale inhibition rate of the compound scale inhibitor prepared in Example 1 is significantly higher than that of Comparative Example 1, indicating that after modification with polyaspartic acid, the temperature resistance of the compound scale inhibitor is significantly improved.

[0060] 3. The scale inhibition rate of the compound scale inhibitor was determined by referring to the national standard "Determination of scale inhibition performance of water treatment agents: calcium carbonate precipitation method" (GB / T 16632-2019). The geothermal fluid taken from a geothermal well in Tianjin was used as the background water body. The main chemical components and contents of the geothermal fluid are shown in Table 1. 240 mg / L CaCl was added to the geothermal water. 2 (Ca 2+ Calculated), 732mg / LNaHCO 3 The scale inhibitor of Example 1 was used under the same reaction conditions, and the pH of the test solution was adjusted to 7, 8, 9, and 10 with sodium hydroxide solution. Figure 5 shown.

[0061] Depend on Figure 5 It can be seen that in alkaline geothermal water with a pH of 7-10, the scale inhibition rate of the compound scale inhibitor prepared in Example 1 is above 85%, and the scale inhibition effect is obvious, indicating that the compound scale inhibitor has good acid and alkali resistance.

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A green compound antiscalant for geothermal fluid, characterized by: The composite antiscalant comprises the following raw materials in parts by weight:

2. The green compound antiscalant for geothermal fluid according to claim 1, characterized in that: The compound antiscalant comprises the following raw materials in parts by weight:

3. The green compound antiscalant for geothermal fluid according to claim 2, characterized in that: The preparation method of the modified polyaspartic acid comprises the following steps: mixing dextran, polysuccinimide and a catalyst, reacting under heating conditions, and washing, filtering and drying the reaction product after the reaction is completed to obtain the modified polyaspartic acid.

4. The green compound antiscalant for geothermal fluid according to claim 3, characterized in that: The catalyst is prepared by mixing p-toluenesulfonic acid and dimethyl sulfoxide; the solid-liquid ratio of p-toluenesulfonic acid to dimethyl sulfoxide is 0.1-0.12 g: 100-120 mL.

5. The green compound antiscalant for geothermal fluid according to claim 3, characterized in that: The mass ratio of the dextran, polysuccinimide and catalyst is 1-1.2g:2-2.5g:100-120mL.

6. The green compound antiscalant for geothermal fluid according to claim 3, characterized in that: The temperature of the heating step is 120-125° C., the time of the reaction step is 20-24 hours; the molecular weight of the dextran is 1000.

7. The green compound antiscalant for geothermal fluid according to claim 2, characterized in that: The preparation method of the highly hydrolyzed polymaleic anhydride comprises the following steps: adding maleic anhydride, sodium hydroxide and ammonium ferric sulfate into deionized water, stirring until completely dissolved, adding hydrogen peroxide dropwise thereto under heating conditions, and cooling to room temperature after the reaction is completed to obtain the highly hydrolyzed polymaleic anhydride.

8. The green compound antiscalant for geothermal fluid according to claim 7, characterized in that: The solid-liquid ratio of maleic anhydride, sodium hydroxide, ammonium ferric sulfate, hydrogen peroxide and deionized water is 400-500g: 100-105g: 0.04-0.06g: 400-500mL: 450-500mL; the mass concentration of hydrogen peroxide is 30%.

9. The green compound antiscalant for geothermal fluid according to claim 7, characterized in that: The temperature of the heating step is 95-100° C.; the time of the reaction step is 3-4 hours; and the speed of the dropping step is 50-60 drops / min.

Citation Information

Patent Citations

  • Preparation method and application method of modified polyaspartic acid scale inhibitor

    CN104231267A

  • Phosphorus-free scale inhibitor for high-hardness water and preparation method thereof

    CN111960556A

  • Polymerization method for regulating molecular weight of polymaleic anhydride

    CN116948072A

  • Compound scale inhibitor for discharging sea tail water as well as preparation method and application of compound scale inhibitor

    CN118754327A

Cited By

  • Easily biodegradable phosphorus-free scale and corrosion inhibitor and preparation method thereof

    CN120328754A

  • Compound scale inhibitor as well as preparation method and application thereof

    CN121800344A